2010
DOI: 10.1177/0192513x10361866
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Downside to Schedule Control for the Work-Family Interface?

Abstract: Using data from a 2007 U.S. survey of workers, this article examines the implications of schedule control for work-family role blurring and work-family conflict. Four main findings indicate that (a) schedule control is associated with more frequent working at home and work-family multitasking activities; (b) the positive association between schedule control and multitasking suppresses the negative association between schedule control and workfamily conflict; (c) the positive association between working at home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
101
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(111 citation statements)
references
References 26 publications
3
101
1
4
Order By: Relevance
“…36 In the standard labor supply model, the decision to work part-time when a worker is unconstrained is due to a high shadow value of time and/or a low wage. Our estimates suggest that job-seekers by and large prefer working 40 hours, even 34 While not mentioned in our focus group, another potential explanation for some workers actually disliking this type of flexibility is that it could lead to more work-family conflict or higher expectations from family members for home production (e.g., Schieman and Young 2010). 35 This value of time is calculated as the amount the worker has to earn per hour in hours 20 through 40 to be indifferent between the 20 and 40 hour-per-week jobs:…”
mentioning
confidence: 80%
“…36 In the standard labor supply model, the decision to work part-time when a worker is unconstrained is due to a high shadow value of time and/or a low wage. Our estimates suggest that job-seekers by and large prefer working 40 hours, even 34 While not mentioned in our focus group, another potential explanation for some workers actually disliking this type of flexibility is that it could lead to more work-family conflict or higher expectations from family members for home production (e.g., Schieman and Young 2010). 35 This value of time is calculated as the amount the worker has to earn per hour in hours 20 through 40 to be indifferent between the 20 and 40 hour-per-week jobs:…”
mentioning
confidence: 80%
“…The physical isolation that can come with working remotely is correlated with feeling less respected by the organization, which weakens organizational identification (Bartel et al 2012). A meta-analysis found that telecommuting can increase work-family conflict due to longer hours (Allen et al 2015) and because it blurs the boundaries between work and family roles (e.g., Schieman & Young 2010, Allen & Shockley 2009, Kossek & Michel 2011. However, paradoxically, telecommuters who are encouraged to create stronger work-life boundaries are less likely to extend themselves in crunch times, possibly increasing the workload of non-telecommuting coworkers (Lautsch et al 2009).…”
Section: Flexibility In Where Work Is Accomplishedmentioning
confidence: 99%
“…Several researchers (e.g. Ashforth et al, 2000;Bielby and Bielby, 1989;Clark, 2000;Desrochers et al, 2005;Karsten, 1995;Nippert-Eng, 1996;Schieman and Young, 2010) addressing the practice of combining commitments and activities in everyday life recognize that the different domains of life are interconnected and overlapping, which results in people constantly combining different, contemporaneous commitments.…”
Section: Balancing Care Work and Leisurementioning
confidence: 99%